Endogenous endothelin-1 signaling contributes to type I collagen and CCN2 overexpression in fibrotic fibroblasts. - Shi-Wen, X; Renzoni, E; Kennedy, L; Howat, S; Chen, Y; Pearson, J; Bou-Gharios, G; Dashwood, MR; du Bois, R; Black, C; Denton, C; Abraham, D; et al. (2007)
Fibrosis is excessive scarring caused by the accumulation of extracellular matrix proteins and is a common end pathway in many chronic diseases. Endothelin-1 is a possible contributor to the persistent fibrotic phenotype of fibroblasts isolated from fibrotic lesions. In this report we used a specific dual endothelin A/B receptor antagonist, bosentan, to determine the role of endogenous endothelin signaling in maintaining the profibrotic phenotype of lung fibroblasts from scleroderma patients. Bosentan treatment of lung fibroblasts cultured from normal individuals and individuals with scleroderma was assessed using Affymetrix genome-wide expression profiling, real-time polymerase chain reaction and Western blot analysis and revealed that approximately one-third of the transcripts elevated greater than two-fold in fibrotic fibroblasts were reduced by Bosentan treatment. Genes whose overexpression in fibrotic fibroblasts that were dependent on endogenous endothelin signaling included the matrix or matrix-associated genes type I collagen, fibronectin and CCN2. The elevated adhesive property of fibrotic fibroblasts was also reduced by endothelin receptor antagonism. Basal expression of collagen, fibronectin and CCN2 and adhesion to matrix was not affected. Thus endogenous endothelin signaling contributes to the fibrotic phenotype of fibrotic fibroblasts, suggesting that antagonizing endothelin receptors may be of benefit in combating fibrotic disease.